An Investigation of E-Learning Readiness in Vocational High School During the Post Pandemic Covid-19: Case from North Sulawesi - Batmetan, Johan Reimon; Katuuk, Deitje Adolfien; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
The COVID-19 pandemic has changed the learning model in vocational high schools in Indonesia, which is usually face-to-face and has been turned into online learning. This learning uses e-learning with several models such as synchronous learning and asynchronous learning drastically without proper preparation. This creates problems in achieving learning outcomes because of many inhibiting factors. This research aims to investigate the readiness of e-learning implemented in vocational high schools during the post COVID-19 pandemic. The method used is the Aydin & Tasci ELR model for measuring the level of e-learning readiness. The results of this research investigation found that the e-learning readiness score was 4.15, which means that vocational high schools in Indonesia are ready to implement e-learning but still need a slight improvement in several factors. These factors are human resources, organization, technology, and infrastructure. This research concludes that vocational high schools in Indonesia are ready to implement e-learning as a supporter of learning in schools.